A Hydrothermally Stable Irreducible Oxide‐Modified Pd/MgAl2O4 Catalyst for Methane Combustion. Issue 42 (18th August 2020) - Yang, Jingyi; Peng, Mi; Ren, Guoqing; Qi, Haifeng; Zhou, Xue; Xu, Jun; Deng, Feng; Chen, Zhiqiang; Zhang, Jingcai; Liu, Kaipeng; Pan, Xiaoli; Liu, Wei; et al.
Abstract: Catalytic combustion is promising in removing trace amounts of CH4 to address serious environmental concerns. Supported Pd‐based catalysts are most effective but often suffer from low stability in applications owing to the water‐vapor‐induced sintering. Herein, we develop a universal strategy to prepare irreducible‐oxide‐modified Pd/MgAl2 O4 catalysts which show high activity and excellent stability against both hydrothemal aging at elevated temperatures and deactivation in long‐term reaction under wet conditions. The addition of irreducible oxides inhibited the deep oxidation of Pd in the oxygen‐rich conditions, which preserved not only the epitaxial structure but also a suitable active phase of Pd‐PdO x on MgAl2 O4, thus promoting both activity and stability. This work provides new insights into the effect of metal–oxide interaction on CH4 combustion and offers an avenue to design hydrothermally stable and active combustion catalysts for industrial applications. Abstract : A highly active and extremely stable Al2 O3 modified Pd/MgAl2 O4 catalyst was developed via forming epitaxially matched Pd‐MgAl2 O4 interface and adding irreducible oxide to alter the reducibility of PdO. The study provides new insight into the interaction between Pd and oxide on CH4 combustion, offering an avenue to construct stable and active combustion catalysts for industrial application.